PANDANGAN KONSELOR TERHADAP KONSELI DALAM PROSES BIMBINGAN DAN KONSELING (Kajian Filosofis Hakikat Manusia Berdasarkan Alquran) - Nursyamsi, Nursyamsi (Jurnal Al-Taujih : Bingkai Bimbingan dan Konseling Islami, 2015)
Counselling as a profession helper, the root of every profession helper lies in the nature of man himself must be understood by the counselor. The counselor must have the knowledge, skills, and support experience and personality. The counselor must have the competence that is built on a philosophical foundation of human nature, with all its potential, strengths and weaknesses in his life as a creature of Allah  Almighty. Academic competence and professional counselors are integrated to build the integrity of the pedagogical, personality, social and professional. Based on the view of human nature, the nature of counseling, not independent and is associated with human nature itself, as a counseling service that helps resolve the problems faced by individuals. If the individual was not able to finish it, then there is a way one way to find a solution, is through counseling.